‘Nature of the year’ in Germany: An effective policy to raise public awareness? - Hilke Hollens‐Kuhr; Sascha Buchholz; Nadja Pernat (People and Nature, 2025)
Abstract Building public awareness for conservation can be done in different ways. However, the impact of the conservation marketing techniques is not well understood. The ‘nature of the year’ award is a public awareness building strategy for conservation in Germany, which aims to draw attention to annually selected species and their habitats. In order to evaluate the success of these campaigns, we utilized citizen science occurrence records from iNaturalist and Observation.org as well as Google tools for a data‐driven analysis of the association between public awareness and the various organisms awarded as ‘nature of the year’ between 2018 and 2021. Of the 31 species studied, only 16 showed a significant increase in either their occurrence records and/or Google search activity. An increase in occurrence records was found particularly for the categories of insect, butterfly and amphibians/reptiles, whereas a higher Google search activity could be demonstrated for the categories of animal, bird, tree and flower. The reasons for this pattern are manifold: they relate to the prevalence of the organism group, the perception of a species by the public and the associated recording behaviour of citizen scientists, the charisma of the species as well as the human and financial resources of the nominating organizations to conduct marketing campaigns for the nominated species. To enhance the campaign's impact, communication efforts should be unified, such as synchronized ‘nature of the year’ award announcements and shared social media content. Further research using conservation culturomics could address the gap in understanding the effectiveness of public conservation policies. Read the free Plain Language Summary for this article on the Journal blog.